Sobre la génesis y evolución de la pedagogía contemporánea. A propósito de la herencia kantiana - Vilanou Torrano, Conrad (Revista Española de Pedagogía, 2018)
Based on the philosophy of Kant, various attempts made in the 19th and early-20th centuries to constitute pedagogy as a scientific discipline are presented. Analysis is made of the educational function of the aesthetic experience according to Schiller, Herbart¿s model, the return of Kant through Natorp¿s regulatory pedagogy and, finally, the constitution of pedagogy as the science of the spirit.
Keywords: pedagogía contemporánea; génesis; herencia kantiana; Revista Española de Pedagogía